(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
One hundred fifty urine samples were collected from urinary tract infection patients. We obtained 40 isolates of Escherichia coli among these clinical samples. A proportion of UTI in females 93 (62%) is higher than that in males 57 (38%). All locally isolates are multi-resistant, the highest rate of resistance was seen with Amoxicillin/clavulanic acid, and Cloxacillin. The results showed high percentage 14(35%) of class C among locally isolates , while only 4(10%) are able to produce Class A ESβL , on the other hand (7/40) and (8/40) were ESβL neither Class A nor Class C Present and ESβL absent respectively , while among the 40 isolates only 7 isolates were Non-Typable. Three types of β-lactamases include ESβLs genes (blaSHV, blaTEM, blaCTX-M) by the use of uniplex PCR assay. The blaSHV was detected in 1 isolates (2.5%) of the UPEC isolates, while for the blaTEM gene the result showed that in 27 detected isolates (67.5%), there is 23 isolates (57.5%) which indicates the prevalence of blaCTX-M gene. The results showed the Co-existence of blaTEM, blaCTX-M in 30% of isolates, while one isolate blaSHV, blaTEM, blaCTX-M in their genome component